The rise of AI in journalism: ethical and practical implications - Hassim, Mohammad Nurhafiz; Mohamad Nasir, Nur Nasliza Arina (Faculty of Communication & Media Studies, 2025)
This study explores the rapid integration of Artificial Intelligence (AI) within journalism, critically examining its ethical and practical implications. Employing a narrative analysis approach, a systematic literature review was conducted across prominent secondary data databases including Scopus, Web of Science, and Google Scholar. Key search terms used were "AI in journalism" OR "automated journalism" OR "robot journalism," "AI ethics in media" OR "journalistic ethics and AI," and "AI practice on news industry" OR "future of journalism and AI." The analysis identifies three main areas of focus: Ethical implications highlight critical issues of bias, credibility, and accountability inherent in AI-driven journalistic practices. Practical implications are discussed in terms of the increased efficiency and cost reduction afforded by AI technologies, contrasted with concerns over potential job displacement within the newsroom. Lastly, the study addresses transparency and trust, exploring audience reception and the broader societal acceptance of AI-generated news. This research aims to contribute to a nuanced understanding of the evolving role of AI in journalism, emphasizing the necessity for balanced ethical considerations alongside technological advancement.